Provision of information about newborn screening antenatally: a sequential exploratory mixed-methods project - Ulph, Fiona; Wright, Stuart; Dharni, Nimarta; Payne, Katherine; Bennett, Rebecca; Roberts, Stephen; Walshe, Kieran; Lavender, Tina (Health technology assessment (Winchester, England), 2017)
Participation in the UK Newborn Bloodspot Screening Programme (NBSP) requires parental consent but concerns exist about whether or not this happens in practice and the best methods and timing to obtain consent at reasonable cost. To collate all possible modes of prescreening communication and consent for newborn (neonatal) screening (NBS); examine midwives', screening professionals' and users' views about the feasibility, efficiency and impact on understanding of each; measure midwives' and parents' preferences for information provision; and identify key drivers of cost-effectiveness for alternative modes of information provision. Six study designs were used: (1) realist review - to generate alternative communication and consent models; (2) qualitative interviews with parents and health professionals - to examine the implications of current practice for understanding and views on alternative models; (3) survey and observation of midwives - to establish current costs; (4) stated preference surveys with midwives, parents and potential future parents - to establish preferences for information provision; (5) economic analysis - to identify cost-effectiveness drivers of alternative models; and (6) stakeholder validation focus groups and interviews - to examine the acceptability, views and broader impact of alternative communication and consent models. Providers and users of NBS in England. Study 2: 45 parents and 37 health professionals; study 3: 22 midwives and eight observations; study 4: 705 adults aged 18-45 years and 134 midwives; and study 6: 12 health-care professionals and five parents. The realist review identified low parental knowledge and evidence of coercive consent practices. Interview, focus group and stated preference data suggested a preference for full information, with some valuing this more than choice. Health professionals preferred informed choice models but parents and health professionals queried whether or not current consent was fully informed. Barriers to using leaflets effectively were highlighted. All studies indicated that a 'personalised' approach to NBS communication, allowing parents to select the mode and level of information suited to their learning needs, could have added value. A personalised approach should rely on midwife communication and should occur in the third trimester. Overall awareness was identified as requiring improvement. Starting NBS communication by alerting parents that they have a choice to make and telling them that samples could be stored are both likely to enhance engagement. The methods of information provision and maternal anxiety causing additional visits to health-care professionals were the drivers of relative cost-effectiveness. Lack of data to populate an economic analysis, confirmed by value of information analysis, indicated a need for further research. There are some limitations with regard to the range of participants used in studies 2 and 3 and so caution should be exercised when interpreting some of the results. This project highlighted the importance of focusing on information receipt and identified key communication barriers. Health professionals strongly preferred informed consent, which parents endorsed if they were made aware of sample storage. Uniform models of information provision were perceived as ineffective. A choice of information provision was supported by health professionals and parents, which both enhances cost-effectiveness and improves engagement, understanding and the validity of consent. Remaining uncertainties suggest that more research is needed before new communication modes are introduced into practice. Future research should measure the impact of the suggested practice changes (informing in third trimester, information toolkits, changed role of midwife). Current Controlled Trials ISRCTN70227207. This project was funded by the NIHR Health Technology Assessment programme and will be published in full in ; Vol. 21, No. 55. See the NIHR Journals Library website for further project information.